2003
DOI: 10.1242/jcs.00322
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin function probed by laser tweezer and single molecule fluorescence in vascular endothelial cells

Abstract: In endothelial monolayers agonist-induced influx of Ca2+ and activities of the actin cytoskeleton have been shown to be crucially involved in regulation of barrier properties. By laser tweezer application we demonstrated that the strength of adhesion of VE-cadherin-coated microspheres to the surface of cultured endothelial monolayers is significantly reduced by treatment with two well-established permeability-increasing compounds,cytochalasin D and the Ca2+-ionophore A23187, which shows that both compounds dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 56 publications
11
104
2
2
Order By: Relevance
“…In contrast, in the case of vinculin, the cell can regulate the assembly of adhesive structures via a cytoplasmic protein complex. Such a regulation can also exist with cadherins as shown by experiments using beads covered with cadherins (20)(21)(22)(23). In this setup, cadherins are not just behaving as glue.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, in the case of vinculin, the cell can regulate the assembly of adhesive structures via a cytoplasmic protein complex. Such a regulation can also exist with cadherins as shown by experiments using beads covered with cadherins (20)(21)(22)(23). In this setup, cadherins are not just behaving as glue.…”
Section: Discussionmentioning
confidence: 94%
“…CytD, but not ALCAM-mediated adhesion, causes activation of RhoA, Rac1 and Cdc42 Disruption of the actin cytoskeleton by CytD treatment results in increased lateral mobility and cluster formation of integrins (Elemer and Edgington, 1994;Lub et al, 1995), cadherins (Baumgartner et al, 2003), and other cell adhesion molecules, such as Ep-CAM (Balzar et al, 1998), leading to increased adhesion. In addition to disrupting the actin cytoskeleton, Ren and co-workers (Ren et al, 1999) showed that in quiescent Swiss 3T3 fibroblasts CytD treatment activates RhoA.…”
Section: Resultsmentioning
confidence: 99%
“…At the later stages of assembly, a submembranous sheet of Dia1-nucleated actin filaments could increase adhesion by reducing the lateral mobility of cadherin receptors in the plane of the membrane; this mechanism does not require a direct link between cadherin receptors and the actin filaments (Baumgartner et al, 2003;Iino et al, 2001;Sako et al, 1998). Another interesting possibility is the actin-polymerizationdependent control of turnover of adhesion receptors.…”
Section: Journal Of Cell Science 120 (21)mentioning
confidence: 99%